Producción y comercialización de plantas medicinales como un alternativa generadora de empleo para pequeños agricultores en la parroquia Fumisa del cantón Buena Fe - Acosta Chávez, Fernando Enrique (2012)
A study was conducted in good faith parish Fumisa enclosure, for the use, knowledge and trade in medicinal plants, combining qualitative and quantitative research techniques and methods, the defined sample included 170 people inhabiting the sector. Data obtained from the consensus of informants, were analyzed by the value index usage (IVU) and the level of significant use (UST) traditional of the Medicine of the Island (TRAMIL). The results indicate that 86% of the population uses plants medicinal, 47 per cent, at ages 21 to 40 years are those that have a greater knowledge. The level of study, sex and duration of residence influences the knowledge about medicinal plants and knowledge transfer occurs from one generation to another. Plants used for medicinal purposes are Matricaria chamomilla l. (Chamomile), Plantago major l., (plantain), Cymbopogon citratus D.C. (herb Louise), Origanum vulgare (oregano), Chenopodium Ambrosioides (paico) and Aloe vera (l.) Burm (Aloe Vera). Most used parts are leaves (73%) fresh (90%), associated way (88%); in either infusions (54%) or crushed (13%) for use in food (seasoning), problems of inflammation, cough and flu, headaches, santeria (bathrooms and cleaning) and purgative. 46% Purchased in the market and grown in small gardens of their homes. There is areas for production and marketing of medicinal plants, but there is the interest of the population to devote to this activity to improve the quality of life of their families, so it considered important to receive training (88%), counseling (79%) on the subject, and partner to produce and market the medicinal plants.